Disruption Model of Mixue’s Marketing Business - Daniel Susilo; Harliantara (Jurnal Ekonomi dan Bisnis Digital, 2023)
Mixue's Ice Cream and Tea became famous in Indonesia through the spread of their branches. They’re predicted to surpass McDonald’s in a few years. Their fast growth drives the reaction that they’re Ruko Kosong hunters, or the hunters of empty shop buildings. With its quick spread, Mixue becomes an important name to be analyzed with SWOT analysis, which would detail how Mixue stands on its own. The name immortality or collective branches has two different sides ever since the existence of Mixue. Mixue is a method whose name in a franchise doesn’t matter.